24.7k views
3 votes
If, g(x)=-2(x+2)-6 what is g(b-5)=

User Msunbot
by
5.3k points

1 Answer

7 votes

The value of
g(b-5)=-2b

Solution:

In the notation g(x) we know that whatever is put in the parentheses is what we replace for x. In the given situation, since it is g(b-5) we have to replace every x in the function with b-5. That is if,


g(x)=-2(x+2)-6

then,
g(b-5)=-2((b-5)+2)-6


\Rightarrow g(b-5)=-2(b-5+2)-6

On solving we get,


\Rightarrow g(b-5)=-2(b-3)-6\rightarrow g(b-5)=-2b+6-6


\Rightarrow g(b-5)=-2b

User Anas Al Hamdan
by
5.4k points